Karakteristik warna crayon dari pemanfaatan ekstraksi limbah kulit buah naga (hylocereus polyrhizus) - Permatasari, Yusintia Ayu; Masrida, Reni; Kustiyah, Elvi (Journal of Biopesticides and Agriculture Technology, 2024)
Background: Crayons are drawing equipment made from colored wax, charcoal, chalk, or other materials used for writing and coloring. Crayons are used in schools throughout the world because crayons are easy to use, do not make dirty, blunt, non-toxic, and have many colors. Findings: Crayons can be used from children to adults. Wax crayons are usually used by children to draw and color. One popular crayon brand is Crayola. Dragon Fruit Skin (Hylocereus polyrhizus) contains anthocyanin which can be used as a natural coloring agent for decorative preparations and also has antioxidant activity. Methods: Dragon fruit skin (Hylocereus polyrhizus) extraction has been carried out by means of dragon fruit peel extracted using the wet maceration method with 70% ethanol. The extract was then made into 2 crayon formulations with concentrations of 25% and 20%, respectively. The crayon formulation consists of paraffin wax and dragon fruit peel extract. The resulting crayons have a brownish color, and aromatic odor typical of dragon fruit peel extract. Conclusion: The results of the topical test obtained the best formula on the formula with the composition of the dragon fruit peel extract 25% and 75% paraffin wax. Based on the results of the topical test, this crayon can be used. It's just that the color and texture of crayons that are easily brittle and oily make the results of this research experiment not as expected.